PENGEMBANGAN LEMBAR KERJA SISWA (LKS) MATERI PECAHAN BERBASIS METODE PENEMUAN TERBIMBING UNTUK KELAS VII SISWA SMP - Adawiah, Robiatul (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2016)
ABSTRACTThe research purpose was to created student worksheets (Lembar Kerja Siswa) base on guided finding method valid and simply fraction substance. Research type used was Research and Development. There were three research steps; those defining, designing and developing. Research subject was 7th grade secondary school students SMP N 2 RAMBAH 2015/2016 school year. Instruments used on research were validation sheets and quesionnaire. The process to get Lembar Kerja Siswa (LKS) that valid and practice involve defining, designing and developing. On the step of developing student worksheets (Lembar Kerja Siswa) four raters validated the student worksheets (Lembar Kerja Siswa) by average 3,17 as valid category. While practicalities got by experiment and research by practicalities quesionnaire expert got 81,25% in practical category. Practical experiment by teacher got 86,64% in very practical category. And practical experiment by 7th grade SMP N 2 RAMBAH got 89,93% in very practical category. Finally, it could be conclude that student worksheets (Lembar Kerja Siswa) based on guided finding method is valid and very practical.